Brain Cortical Complexity and Subcortical Morphometrics in Lifelong Premature Ejaculation - Lu, Jiaming; Yuan, Lihua; Jin, Jiaxuan; Yang, Shangwen; Zhang, Wen; Li, Ming; Zhang, Xin; Wang, Junxia; Wu, Sichu; Chen, Qian; Qing, Zhao; Dai, Yutian; et al. (Frontiers in Human Neuroscience, 2020)
Premature ejaculation (PE) is the most common male sexual dysfunction. The brain disturbances that cause this disorder remain poorly understood. The aim of this study was to investigate how the morphology of cortical and subcortical brain structures differed in PE, how these morphologic differences were associated with severity measures of PE, such as intravaginal ejaculatory latency time (IELT), and how these cortical and subcortical structures were causally connected through a mediation analysis. Anatomical MRI scans were acquired from 39 male participants, 23 with PE (28.78±4.32 years), and 16 without PE (27.88±3.65 years). We used a subcortical analysis package within FSL to perform subcortical shape segmentation and statistical analysis. The PE group was compared with the normal control group in the shapes of 15 subcortical structures with general linear models (p < 0.05, family-wise error (FWE)-corrected). We analysed the cortical complexity revealed by the gyrification index using the Computational Anatomy Toolbox (CAT12). Vertex-wise shape analyses revealed outward shape deformations (expansions) in the left hippocampus and bilateral thalamus. Gyrification index analyses revealed that the right orbital frontal cortex and the right nucleus accumbens had greater complexity in PE patients. The shape deformations were positively correlated with the IELTs in the normal control (NC) group, while this relationship was interrupted in the PE group. PE is associated with outward deformations of the subcortical surfaces and more complexity of the cortical structures. These morphological differences may be the basis of the brain functional alterations underlying PE.